2003
DOI: 10.1021/jm0308904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of 3D-QSAR CoMSIA Models for CDK1, CDK5, and GSK-3 Inhibition by Paullones

Abstract: With a view to the rational design of selective GSK-3beta inhibitors, 3D-QSAR CoMSIA models were developed for the inhibition of the three serine/threonine kinases CDK1/cyclin B, CDK5/p25, and GSK-3beta by compounds from the paullone inhibitor family. The models are based on the kinase inhibition data of 52 paullone entities, which were aligned by a docking routine into the ATP-binding cleft of a CDK1/cyclin B homology model. Variation of grid spacing and column filtering were used during the optimization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 56 publications
(107 reference statements)
1
59
0
Order By: Relevance
“…Besides, studies have shown that receptor-guided alignment produced better results than those from a ligand-based approach due to its more realistic information about the receptors. 55,56 Therefore, we adopted a receptorguided alignment by employing the docked conformation of the most active compound (Fig. 2C).…”
Section: Comsia Statistical Resultsmentioning
confidence: 99%
“…Besides, studies have shown that receptor-guided alignment produced better results than those from a ligand-based approach due to its more realistic information about the receptors. 55,56 Therefore, we adopted a receptorguided alignment by employing the docked conformation of the most active compound (Fig. 2C).…”
Section: Comsia Statistical Resultsmentioning
confidence: 99%
“…In order to evaluate the efficacy of the chosen model, 11 highly active compounds including the paullones, 5 the indirubins 4 and some compounds with similar structures to the ones in the training set were selected and tested and the experimental activity (from literature) and the estimated activity are shown in Table 5 . However, this hypothesis can not be satisfactory to evaluate the activity of the indirubins (such as compound 100), maybe the binding style of this kind of compounds with GSK-3 is different from that of the other inhibitors.…”
Section: Activity Predictionmentioning
confidence: 99%
“…Nowadays, several classes of adenosine triphosphate (ATP) competitive or noncompetitive GSK-3 inhibitors have been reported such as maleimide derivertives, 3 indirubins, 4 paullones, 5 staurosporine, 6 aloisines, 7 hymenialdisine 8 and thiadiazolidinones (TDZD). 9 The 3D structure of GSK-3 and the cocrystallographic data of GSK-3 with its inhibitors have been published, which makes it feasible to carry out rational drug design.…”
Section: Introductionmentioning
confidence: 99%
“…to the sodium salt of the amino ester 4a (to enhance the nucleophilicity of the nitrogen atom) at room temperature, the desired amide 9 was obtained in 57% yield. Similarly, 1-methylindole-2-carbonyl chloride (8), prepared from 6, was treated with 4a to give amide 10 in excellent yield (96%). In this last reaction, only 1.5 equiv.…”
Section: Access To Pentacyclic Indole Derivativesmentioning
confidence: 99%
“…Recently, Erba and co-workers described the preparation of a similar indole analogue A, in which the pyrrolo [1,2-c] [1,4]diazepine moiety was obtained from 2-amidinylindole-3-carboxaldehyde. [6] The sevenmembered lactam moiety is also encountered in potent glycogen synthase kinase-3 (GSK3) and/or cyclin-dependant kinase inhibitors such as paullones, [7,8] hymenialdisine [9Ϫ15] and 5-(arylhydrazono)-3,4,5,10-tetrahydro-2H-azepino [3,4-b]indol-1-one. [16,17] For our part, we have reported the synthesis of the first pyrrolo[1,2:1Ј,2Ј]azepino [6,5-b]indole-1,5-dione framework B from indole-2-carboxylic acid and ethyl pyrrolidin-2-ylacetate through an unusual cyclisation reaction.…”
Section: Introductionmentioning
confidence: 99%